A Historic Waterfront Revitalisation Project in Tanjung Emas, Johor - Asmawi, M. Zainora (KAED, 2019)
This project addresses the importance of public open spaces in supporting the revitalisation of historic waterfront development along Tanjung Emas, Muar, Johor. At the domestic level, this place is popular as it attracts many visitors, particularly on weekends. Its location in the Royal Town of Bandar Maharani; thus, it plays an essential role in creating a catalyst for a sharp image of urban design elements. The distribution of many historical buildings such as Masjid Sultan Abu Bakar, Muar High School, and Muar District Court, reflecting the influence of colonial architecture adds to its colourful and vibrant image of an old town. Hence, the proposals which mainly cover the public open spaces along Tanjung Emas are expected to revitalise the image of Bandar Maharani. The projects involve mainly the uplifting the facilities of the children playground, provision of the water fountain, open theatre, pavilion, and floating café.